Impact of sports arenas on land values: evidence from Berlin. - Ahlfeldt, P. Gabriel M.; Maennig, Wolfgang (My University, 2007)
Das Papier wendet ein hedonisches Preismodell zur Erklärung der Grundstückspreise in Berlin an. Das Modell bewertet die Wirkungen dreier Multifunktionssporthallen in Berlin-Prenzlauer Berg, die zur Attraktivitätssteigerung des vernachlässigten Stadtteils geplant und gebaut wurden. Die empirischen Ergebnisse belegen die Wirkungen der verschiedenen Qualitätseigenschaften der Bauten auf den Bodenwert. Bestätigt wird die These, dass Sportstätten eine signifikante Auswirkung innerhalb eines Radius von 3000 Metern haben. Die Wirkungsmuster und -grade können allerdings unterschiedlich ausfallen, je nach dem, ob bei der Planung mögliche negative Auswirkungen (Parkplatznot, Lärm durch Sportveranstaltungen) kompensiert werden konnten.

The paper employs a hedonic price model to explain standard land values in Berlin. Impact on land values is assessed for the two city airports situated in Berlin, Germany, Tempelhof and Tegel. Empirical results confirm expectations about the impact of various attributes on land values. Areas exposed to noise pollution of downtown airport Tempelhof sell at a discount of approximately 5-9% within a distance of 5000 m along the air corridor. No significantly negative impact was found for land values around Tegel Airport, which is located in a central, but less densely populated, area. Market access indicators created for all three Berlin airports in operation, including Berlin Schoenefeld International Airport, reveal clear location advantages in terms of accessibility of Tempelhof and Tegel compared to Schoenefeld Airport, where the new Berlin Brandenburg International Airport is about to be developed.
Keywords: Standort; Sportstätte; Stadion; Bodenwert; Bodenpreis; Grundstückswert; Externe Effekte; Immobilienmarkt